Arthropods as vectors of animal diseases in Malaysia - a short review - Fadzil, M. (Persatuan Doktor Veterinar Malaysia, 1986)
The literature on work done in Malaysia on the role of arthropods as vectors of animal diseases is reviewed. The mosquitoes, midges, tabanids, buffalo fly, stable fly, haematophagous muscid and ticks have a role to play in the transmission of pathogens of animal diseases in this country. More studies in this field are encouraged